2011
DOI: 10.19030/ajbe.v4i9.5618
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Of The Differences Between Student Age And Social Networking Utilization Within A School Of Business

Abstract: <span style="font-family: Times New Roman; font-size: small;"> </span><p style="background: white; margin: 0in 0.5in 0pt; text-align: justify; mso-pagination: none;" class="MsoNormal"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">Social networking sites such as Facebook, LinkedIn, and Twitter are widely regarded as an exciting opportunity to communicate with friends, especially for college students. The overall response to social networking tends to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…For instance, Poelhuber and Anderson (2011) examined the use of social media and other collaboration tools in the context of distance learning and found that males and younger students have more positive attitudes toward technology as well as greater experience with social media. Zula, Yarrish, and Pawelzik (2011) explored the use of social networking tools in business education and found that younger students (18-20 years old) spent less time on career exploration research than older students (21-24 years old) but found no significant difference with regard to time spent on social networks in general.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Poelhuber and Anderson (2011) examined the use of social media and other collaboration tools in the context of distance learning and found that males and younger students have more positive attitudes toward technology as well as greater experience with social media. Zula, Yarrish, and Pawelzik (2011) explored the use of social networking tools in business education and found that younger students (18-20 years old) spent less time on career exploration research than older students (21-24 years old) but found no significant difference with regard to time spent on social networks in general.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Peluchette and Karl (2010) point out that Facebook is the leading site for college students. It is therefore not surprising that academicians have considered the potential of Web 2.0 tools such as social networking media (e.g., Facebook, MySpace, Twitter) for enhancing education (Blankenship 2011, Galagan 2009, Granitz and Koernig 2011, Greenhow et al 2009, Wankel 2009), as well as post-graduation employment (Zulu et al 2011). However, Karl and Peluchette (2011) report evidence that a large number of students remain suspicious and uneasy about friend requests from faculty members.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research has already confirmed the homogeneity of students regarding their active involvement in social networks when it comes to a pedagogical approach to teaching (Hargittai and Litt, 2011), but also an important conclusion that all the millennials (18 to 20 years of age group), as well as those from the 21 to 24 years of age group, spend almost the same amount of time on social networks (Zula et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 71%